2019
DOI: 10.1186/s12966-019-0892-4
|View full text |Cite
|
Sign up to set email alerts
|

Isotemporal substitution of inactive time with physical activity and time in bed: cross-sectional associations with cardiometabolic health in the PREDIMED-Plus study

Abstract: BackgroundThis study explored the association between inactive time and measures of adiposity, clinical parameters, obesity, type 2 diabetes and metabolic syndrome components. It further examined the impact of reallocating inactive time to time in bed, light physical activity (LPA) or moderate-to-vigorous physical activity (MVPA) on cardio-metabolic risk factors, including measures of adiposity and body composition, biochemical parameters and blood pressure in older adults.MethodsThis is a cross-sectional anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 48 publications
9
29
1
1
Order By: Relevance
“…These ndings are consistent with previous cross-sectional research in adult populations [3,32,40], which have found a hazardous relationship between SB and markers of body composition, including body fat, VAT and muscle mass [3,9,32,40,41]. The present results showed that greater SB is associated with greater body fat and lower muscle mass in an aging population, resulting in greater cardiometabolic risk and disability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These ndings are consistent with previous cross-sectional research in adult populations [3,32,40], which have found a hazardous relationship between SB and markers of body composition, including body fat, VAT and muscle mass [3,9,32,40,41]. The present results showed that greater SB is associated with greater body fat and lower muscle mass in an aging population, resulting in greater cardiometabolic risk and disability.…”
Section: Discussionsupporting
confidence: 93%
“…Data extracted from the GENEActiv was clustered as IT in bouts of 1 minute (< 1.5 METs), LPA (1.5-3 METs), MVPA (> 3 METs) and time in bed (time difference between going to bed and leaving) [29][30][31]. Details of how the PA and IT were processed have been described [32] previously. Accelerometer measures were taken at baseline, 6-and 12-months follow-up.…”
Section: Accelerometer Measured Physical Activity and Inactive Timementioning
confidence: 99%
“…Conversely, participants with the lowest MetSSS (T1) showed lower levels of sedentary time and depression risk and higher total LTPA, and they tended to have an anti-inflammatory dietary pattern and tended to have higher adherence to MD. Concretely, T3 participants showed lower carbohydrate and nut intake and moderate and vigorous LTPA, which is associated with higher risk of CVD [4,5,25]. Conversely, T3 showed higher intake of protein, SFA, TFA, cholesterol, as well as higher consumption of red and processed meat, and other oils different from olive oil and spirits compared with T1, resulting in an increased risk of several major chronic diseases [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence has shown that high amounts of sedentary behaviour are associated with increased risks of several chronic conditions and mortality [5,6,38]. Prolonged TV viewing time is associated with an increased risk of type 2 diabetes mellitus (T2DM), CVD, and all-cause mortality [36].…”
Section: Sedentary Behaviour and Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation